Акт злуки УНР і ЗУНР - знакова подія української історії - Сеньків, Михайло; Senkiv, Mykhailo (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано боротьбу ЗУНР за її злуку з УНР. Показано, що 3 січня 1919 р. Національна рада прийняла ухвалу «Про злуку ЗУНР з УНР», а 22 січня 1919 р. у Києві на майдані Святої Софії відбулася урочиста церемонія злуки. Наступного дня Трудовий конгрес УНР затвердив Маніфест про злуку. Однак у зв’язку з тодішними воєнно-політичними обставинами, ідеологічними розбіжностями між галичанами та наддніпрянцями, а також через відсутність міжнародної підтримки не вдалося українські землі об’єднати.

In the article it has been the struggle of the West Ukrainian People’s Republic for the union with the Ukrainian People’s Republic. It has been shown that on January 3, 1919 the Ukrainian National Council proclaimed ‘the Act of the Union of the West Ukrainian People’s Republic with the Ukrainian People’s Republic’, and on January 22, 1919 there was a ceremony of the Union on the St. Sophia’s square in Kyiv. The next day the Labour Congress of the Ukrainian People’s Republic approved the Manifesto of the union and delegated new members into the National Council. The West Ukrainian People’s Republic was renamed into ‘the Western region of the Ukrainian People’s Republic’. But because of the military, political situation and the ideological differences between the Galicians and the Dnieper Ukrainians, the union of the Ukrainian lands failed because of the lack of the international support.
Act of Unification of UPR and ZUNR - a significant event of the Ukrainian history
Keywords: Акт злуки; соборність українських земель; перевступний договір; ЗУНР; УНР; the Act of the Union; the unity of Ukrainian lands; the preliminary agreement; the West Ukrainian People’s Republic; the Ukrainian People’s Republic